Kualitas Udara Ambien Sulfur Dioksida (SO2) Terminal Bus di Kota Manado: Studi Ekologi - Syalom Mikha Tiwa; Oksfriani Jufri Sumampouw; Budi Tamardy Ratag (Sam Ratulangi Journal of Public Health, 2024)
Background: The Karombasan Terminal is a terminal located in Manado City and has dense transportation activities and has the potential to contribute a lot of air pollution from the burning of fuel oil. There are human activities, both passengers, bus/public transportation crews, and traders around the terminal who are at risk of exposure to SO2. The existence of traders who have stalls/canteens in the terminal area makes traders an object at risk of being affected by air pollution. The purpose of this study is to measure SO2 levels in ambient air at the Karombasan terminal in Manado city in 2024. Methods: This study is a descriptive research conducted at the Karombasan terminal, Manado City in September 2023 – July 2024. The subject of this study is ambient air with SO2 parameters. The primary data of this study is data obtained from the measurement of ambient air SO2 concentration at the research site with the help of SGS WLN Manado City. Univariate data analysis. Research Results: The results of this study showed that the ambient SO2 levels of air obtained ranged from <20-33 μg/Nm3. The highest SO2 level of 33 μg/Nm3 was found at point 1 day II and the lowest level of <20 μg/Nm3 was found at several points, namely point 2 (morning and afternoon) day I and II. Conclusion: The conclusion of this study is that the ambient SO2 level of air at the Karombasan Terminal ranges from <20-33 μg/Nm3 where this value is still below the NAV, which is 150 μg/Nm3. Therefore, it is necessary to regularly and comprehensively monitor the air quality at the Karombasan terminal so that efforts can be made to prevent environmental and public health impacts.